Conservation laws and a new expansion method for sixth order Boussinesq equation - Yokus, Asif; Kaya, Dogan (Amer Inst Physics, 2015)
In this study, we analyze the conservation laws of a sixth order Boussinesq equation by using variational derivative. We get sixth order Boussinesq equation's traveling wave solutions with (1/G')-expansion method which we constitute newly by being inspired with (G'/G)-expansion method which is suggested in [1]. We investigate conservation laws of the analytical solutions which we obtained by the new constructed method. The analytical solution's conductions which we get according to new expansion method are given graphically.
International Conference on Advancements in Mathematical Sciences (AMS) -- NOV 05-07, 2015 -- Antalya, TURKEY
Keywords: Sixth-order Boussinesq equation; Traveling wave solutions; Nonlinear partial differential equation; Conservation laws